Investigating the Impact of Viral Infections on Pharmacokinetics and Pharmacodynamics of Antiviral Drugs - Anand Prakash (International Journal of Virus Studies, 2024)
The emergence and re-emergence of viral infections pose significant challenges to public health, necessitating a comprehensive understanding of how these infections impact the pharmacokinetics and pharmacodynamics of antiviral drugs. This review explores the intricate interactions between viral pathophysiology and the pharmacological effects of antiviral agents. Factors such as viral replication dynamics, host immune responses, and the genetic variability of both viruses and hosts significantly influence drug absorption, distribution, metabolism, and excretion. Furthermore, the review highlights the clinical implications of these interactions, including the emergence of drug resistance and the variability in therapeutic outcomes among patients. This article aims to synthesize current knowledge on these interactions, providing insights into future directions for antiviral drug development and clinical practice. The incorporation of novel techniques such as CRISPR-based antiviral therapies, broad-spectrum antivirals, and AI-driven drug discovery could lead to transformative changes in the management of viral diseases, allowing for more resilient and flexible antiviral regimens. Future research and development efforts must continue to integrate these innovations while addressing the dynamic nature of viral pathogens and the growing prevalence of drug resistance.
Keywords: Antiviral drugs; Pharmacogenomics; Pharmacokinetics; Precision medicine; drug delivery systems; drug resistance; host-pathogen interactions; pharmacodynamics; therapeutic outcomes; viral infections